An Analysis of the Utilisation of Audiovisual Archives in Higher Humanities and Arts Education - Klodner, Michal; Udvardyová, Lucia (Teorie vědy / Theory of Science, 2010)
Audiovisual archives with an advanced communication infrastructure are a rapidly developing tool whose unique potential in the realm of education has not been sufficiently explored yet. Archive system technologies already incorporate numerous collaborative functions. This paper aims to present quantitative and qualitative results of a research project undertaken at the Film and TV School at the Academy of Performing Arts. Through several focus groups – users of new media-oriented web portal Konvergence.info, professionals working with audiovisual archives and students of FAMU, usage of audiovisual material in the particular groups was examined. The research was based on selecting the best tools for scientific collaboration in terms of audiovisual content and in researching the utilisation of their certain groups, such as functions for annotating audiovisual content and personal knowledge organisation. These days the cooperation between education and research does not rest in transfer of completed knowledge but in the capability of their sharing in the process of their formation which enables a dialogue and translation between the various specializations. This leads to new knowledge and a more effective solution of problems. The objective thus was to find such a combination of technologies and a working methodology that would facilitate unique talent and interests as well as strengthen the sense of cooperation and communication in a heterogeneous collective.